2016
DOI: 10.3390/su8050445
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Emissions and Cost by Floor Types of Public Apartment Houses in South Korea

Abstract: Abstract:In each country in the world, there is a strong need for all industries to reduce CO 2 emissions for sustainable development as a preparation for climatic change. The biggest issue in many developed countries, including the United States, is to reduce CO 2 emissions for the upcoming implementation of Carbon Emissions Trading. The construction industry, in particular, which accounts for up about 30% of CO 2 emissions, will need studies on the amount of CO 2 emissions. The purpose of this study is to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Reducing the number of levels is not financially feasible when considering the overall floor space per lot. Nevertheless, studies have shown that this benefit is no longer present above 20 levels [61].…”
Section: Recommendationsmentioning
confidence: 99%
“…Reducing the number of levels is not financially feasible when considering the overall floor space per lot. Nevertheless, studies have shown that this benefit is no longer present above 20 levels [61].…”
Section: Recommendationsmentioning
confidence: 99%
“…However, the wall column structure system has been changed to the rahmen structure again because the wall column structure was effective in terms of workability and economy, but the variability was disadvantageous. So, the target of this research is the wall column structure system with reinforced concrete constructed in the 1980~2000s (Bang & Park, 2017;Jang, Kim, & Chae, 2016).…”
Section: Literature Review 1general Characteristics Of Renovation Comentioning
confidence: 99%